Fragmentation Reactions of Labeled and Unlabeled Rhodamine B in a High-Resolution Fourier Transform Ion Cyclotron Resonance Mass Spectrometer. Issue 2 (April 2013) - Clemen, Martin; Gernert, Claus; Peters, Jonathan; Grotemeyer, Jürgen
The fragmentation reactions of Rhodamine B have been investigated by the use of electrospray ionization mass spectra in a high mass resolving ion cyclotron resonance mass spectrometer. Using high resolution, it could be shown that the loss of 44 mass units from the molecular ion is due to propane; the measured masses were inconsistent with loss of carbon dioxide. These conclusions are supported using deuterium-labeled Rhodamine B. This sample again only shows the loss of fully-deuterated propane verifying the high-resolution data. These findings illustrate very clearly that the conclusions based solely on low resolution spectra were false. The general implication on fragmentations of aromatic acids is discussed.